Late-onset Group B Streptococcal Meningitis in a Neonate With Early Antibiotic Prophylaxis - Ting-Jung Ko; Wu-Shiun Hsieh; Po-Ren Hsueh; Hung-Chieh Chou; Chun-Yi Lu (Pediatrics and Neonatology, 2010)
An otherwise healthy female baby who had received early postnatal antibiotic prophylaxis because of maternal vaginal group B streptococcal (GBS) colonization died of late-onset GBS meningitis. GBS was isolated from blood and cerebrospinal fluid. Genotyping using pulsed-field gel electrophoresis confirmed that the GBS isolates from the patient were identical to those from her mother's vagina. Susceptibility tests demonstrated no antibiotic resistance. This report provides additional microbiologic evidence indicating that early postnatal antibiotic prophylaxis is not effective in preventing late-onset GBS infections in neonates born to mothers with GBS colonization.